Training volunteers, in protection and civil defense, through the training center for emergencies and disasters of the civil defense secretariat of Nova Iguaçu, between 2017 and 2023 - Moura, Claudia Avelar Barboza Lima; Filho, Sebastião dos Reis Soares; Januzzi, Carlos Augusto da Silva; Costa, Lucas Onofre; Reis, Felipe Azevedo de Araújo; Santos, Vitória Clem Belchior dos (Seven Editora, 2024)
This scientific article presents the advantages of a tool created for the professional activity of training volunteers from the community in general, who will be supporting, after being trained, a Municipal Coordination of Protection and Civil Defense (COMPDEC) of Nova Iguaçu, characterized in the research, by the Municipal Secretariat of Civil Defense of Nova Iguaçu (SMDC-NI), acting in prevention, preparedness and response, when in risk reduction and accident and disaster management. The work was aimed at presenting the advantages of the existence of the Training Center for Emergency and Disaster (CETRED) in the qualification of volunteers. Thus, we sought to study the role of volunteering in civil protection and defense in Brazil. An attempt was made to verify the type of disaster with the greatest relevance in the municipality studied, Nova Iguaçu, which presented the greatest importance, in terms of damages and losses, the forest fires. And then, it was followed by the analysis of the planning and performance and development of the so-called Training Center for Emergencies and Disasters (CETRED), when focused on professional education in the training of volunteer agents in civil protection and defense. The research methodology was qualitative, through a bibliographic, documental and descriptive research, with researchers exploring in loco the actions and activities listed, from where they obtained data, from the courses and practical actions, involving the target audience; whose results were discussed, were scored for use, as a standard, to the other Municipal Coordination of Protection and Civil Defense, at the national level. Concluding positively to the importance of the tool created, even though there are difficulties to be observed and overcome in its implementation and implementation. DOI:https://doi.org/10.56238/sevened2024.007-020